The influence of personal traits and dynamic leadership on work productivity with resilience as a moderator - Keradjaan, Herson (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2026)
The study aims to look at the direct influence of personal traits, dynamic leadership and resilience on work productivity, as well as the moderate impact of resilience on the influence of personal traits and dynamic leadership on work productivity. The research sample is employees who have worked productively every day. The study uses a structural equation modeling approach, with a moderated regression analysis method, using Smart PLS. The results of the study prove that personal traits, dynamic leadership and resilience have a positive effect on work productivity. Resilience strengthens the influence of personal traits on work productivity. The implication is that if you want to increase employee work productivity, the main priority strategy recommended is to increase dynamic leadership, the second priority is with the strategy to improve personal traits, and the third priority is with the strategy to increase employee resilience. These two things are very effective for increasing work productivity. Another alternative to increase work productivity is to synergize strategies through the collaboration of personal traits and resilience skills. By combining personal traits with the resilience ability of employees, employee work productivity will also increase significantly.